Experimental model of gastroesophageal reflux in rats - Gaia Filho,Edmilson Vieira (2005)
PURPOSE: To develop an experimental model of gastroesophageal reflux in rats. METHODS: Sixty Wistar rats underwent surgery and were assigned to one of the three groups of twenty animals each. The animals in group A underwent total esophageal myectomy and, in group (B), underwent partial myectomy. The third group was the control group (C). A contrast radiographic study of the esophagus was performed to evaluate gastroesophageal reflux. The anatomopathological study of the esophagus was used to evaluate esophagitis. RESULTS: During the 30-day postoperative follow-up, 14 animals in group A presented with reflux of barium in the esophagus. The presence of barium in the esophagus was observed in 7 animals in group B and in 2 animals in the control group. The result of the histopathology examination was controversial. A marked weight loss in the rats undergoing total myectomy was observed, however there was no significant statistical difference. CONCLUSION: Total myectomy in the lower third of the esophagus caused gastroesophageal reflux in the majority of the animals.